Development of Gudang House Design for Domestic and Agricultural Water Supply in Drought Adaptation - Sugiarto, Ari; Syafriyandi, Debby; Yovanda, Ridho (Civil and Environmental Science Journal (CIVENSE), 2026)
The design development of the Gudang house for drought adaptation can include a rainwater harvesting system on the roof. The purpose of this study was to develop and test the success of a rainwater harvesting design and irrigation system in a Gudang house to meet domestic water supply and small-scale agriculture in drought adaptation. The stages of the research were divided into climate data studies, analysis of domestic water needs and small-scale agriculture, integration of rainwater harvesting and small-scale agriculture designs in the Gudang house, and simulation of water flow fluids in the rainwater harvesting system and planting media. The results of the study showed that the design of the irrigation system in the planting media was able to irrigate plants for up to 7.06 days. The probability of rainfall with a return period of 2 years (Rprob with T=2 years) and the average catchment discharge of rainwater harvesting for all zones is 47.14 m3/month. This discharge was sufficient to meet the domestic water supply and small-scale agriculture at the Gudang house, and the material was still sufficient to meet the water supply for one more house. The simulated discharge at the outlet of storage tank 1 was 1.236 × 10-5 m3/s, whereas the outlet discharge of storage tank 2 was 1.734 × 10-5 m3/s, indicating that storage 2 was filled faster than storage 1. However, with the designed system, Storage 1 and 2 are connected to each other through pipes so that their capacities will be filled equally. The innovation of rainwater harvesting systems and integrated small-scale agricultural systems in the Gudang house can be a promising solution for future drought adaptation.